Two dimensional temperature distribution model in human dermal region exposed at low ambient temperatures with air flow - Gurung, DB (Kathmandu University Journal of Science, Engineering and Technology, 2013)
This paper deals with thermo-regulation in human dermal part in a cold atmosphere with significant air flow. The mathematical model involving bio-heat equation has been solved using finite element method and Crank-Nicolson technique to numerically investigate two dimensional temperature distributions. The natural three layers of dermal part – epidermis, dermis, and subcutaneous tissue are considered for the study. The important parameters like blood mass flow rate, metabolic heat generation rate and thermal conductivity are taken distinct in each layer according to their distinct sub-regional activities. The human subject is assumed in static condition. The wind speed is considered in the range from the start of forced convection (? 0.2 m/s) and up to 5 m/s. The loss of heat from the skin surface to the environment is taken due to convection, radiation, and insensible perspiration. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 11-24 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7320